Bu-Qizza, Numan. “Towards a Genuine Cultural Project on the Thought of Ibn Ḥazm al-Andalūsī,” Year 5, Issue 18 (Fall 1420 AH/ 1999 CE), Pp. 89-102. - بوقزة, نعمان (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1999)
Numan Bu-Quizza’s article attempts to answer whether the Ẓāhiriyyah is a school of thought or an alternative cultural project? It discusses the epistemological theory according to Ibn Ḥazm, its origins and dimensions, features of Ibn Ḥazm’s rational methodology and scientific thinking, his position towards logic and philosophy, and his critique of qiyās (analogy) as a fundamental source of Shariʿah. It also explains the concept of evidence and authority in the theory, Ibn Ḥazm’s Ẓāhiriyyah in light of the concept of bayān, and it concludes by holding that Ibn Ḥazm had recognized the nature of the predicament in which the Ummah at his time was in, and that an intellectual revivalist revolution was needed, one that is based on critique of uṣūl al-fiqh by the process of ta’ṣīl (referral to principal Islamic sources), and discarding the wrong choices that Muslim civilization is still captive to until today.